2017
DOI: 10.1259/dmfr.20170126
|View full text |Cite
|
Sign up to set email alerts
|

Depression of the maxillary sinus anterior wall and its influence on panoramic radiography appearance

Abstract: The diagonal line on a panoramic image was verified to be related to depression of the maxillary sinus anterior wall, and its panoramic image appearance can be altered depending on the position of the tomographic image layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The insertion of dental implants into the maxillary sinus is the most common complication that occurs in the maxilla, and various studies have been conducted on the shape of the maxillary sinus associated with implant placement. In addition, various studies have been conducted on the factors affecting the size and shape of the maxillary sinus and their influence on panoramic features [ 6 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The insertion of dental implants into the maxillary sinus is the most common complication that occurs in the maxilla, and various studies have been conducted on the shape of the maxillary sinus associated with implant placement. In addition, various studies have been conducted on the factors affecting the size and shape of the maxillary sinus and their influence on panoramic features [ 6 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yoshida et al revealed the influence of depression of the maxillary sinus anterior wall on panoramic radiographic appearance [ 17 ]. They showed that the diagonal line on a panoramic image was related to the depression of the anterior wall of the maxillary sinus.…”
Section: Discussionmentioning
confidence: 99%
“…Four videos wrongly identified the posterior wall of the maxillary sinus, with half of them pointed at the zygomatic process of the maxilla (abovementioned) and the other half of them pointed at the diagonal line related to the depression of the anterior wall of the maxillary sinus. This depression is seldom covered by the literature, and readers can refer to [ 25 ] for its radiographic manifestation on panoramic radiography. It might be constructive for students to learn from errors, only if the errors could be identified and rectified [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 However, interpreting the detected conditions and lesions may be challenging because of superimpositions caused by the complexity of the 3-dimensional anatomic structures on the panoramic image. 4 Computer-aided diagnosis systems have been developed to prevent clinicians from overlooking dental diseases and to increase the accuracy of radiological diagnoses. 5 In recent years, computer-aided detection or diagnosis systems created by conventional methods have been replaced by artificial intelligence (AI)-based systems aiming to enhance radiological diagnoses.…”
Section: Introductionmentioning
confidence: 99%